Differential Induction of Proteins in Anopheles gambiae sensu stricto (Diptera: Cullicidae) Larvae in Response to Heavy Metal Selection - Mireji, Paul O. (2006)
Investigations were conducted to establish the magnitude and pattern of differential expression of proteins due to generational selection of third instar An. gambiae s.s. larvae by cadmium, copper and lead heavy metals, three possible common urban pollutants. A susceptible strain of An. gambiae s.s. third instar larvae was separately placed under selection pressure with cadmium, copper and lead at LC(30) and controls through five generations. First, third and fifth generation selection survivors were screened for differentially expressed proteins relative to non-exposed control by two-dimensional gel electrophoresis. Distribution patterns of the spots were analysed by Chi Square or Fishers exact test and variations in expressions between and within generation by ANOVA. Most differentially expressed spots were acidic and of low molecular weight among all metals and generations. Type of heavy metals and generation were main indicators of variations in differential expressions. Variation between generations was most significant among cadmium-selected populations of which most number of spots were induced in the fifth generation. Most spots were induced in the copper-selected population in the third generation. The induced protein spots may be products from respective genes that respond to heavy metals and counter their toxicity, thus building An. gambiae s.s. tolerance to these pollutants. The differential pattern and magnitude of expressed spots has potential application as molecular markers for assessment of anopheline adaptation status to heavy metals, and provide insight into the extent of environmental pollution.